KNOWLEDGE LEVELS OF NURSES ABOUT OXYGEN THERAPY IN TURKEY - Ebru EREK KAZAN (Rojan GÜMÜŞ, 2020)
Oxygen therapy, when duly performed, is very useful. On the other hand, when performed inappropriately, it has significant adverse effects in addition to its therapeutic characteristic. Therefore, the nurses have to have enough knowledge of oxygen therapy. Aim: The aim of this descriptive study is to determine the level of knowledge of nurses regarding oxygen therapy. Methods: The research sample consisted of 302 nurses who agreed to participate in the research, working in a state hospital in Ankara/Turkey. The data have been collected by an descriptive characteristics form and a knowledge test of 40 questions regarding oxygen therapy. Results: In the study that the knowledge level score average of the nurses is =22.94±4.5 (min=8, max=35). The knowledge levels score averages of the nurses have lower than expected and nurses' knowledge is particularly inadequate in terms of oxygen therapy application methods. In this research, the nurses over the age of 45, working in the same department for more than 14 years and working in the operating room have had lower scores (p0.05). Conclusion: In order to enhance the level of knowledge of nurses, it is recommended to provide more comprehensive oxygen therapy education at hospitals and undergraduate level. It is thought that the results of the study shall contribute in determining the educational needs of nurses for oxygen therapy and be a guide for future researches.